Bumping Windows between Monitors - Regan, Tim; Czerwinski, Mary; Meyers, Brian; Smith, Greg (2003)
Users’ move from single to multiple monitors so that they can use more screen real estate. This increase enables them to keep a greater number of windows open and visible at the same time. But there is a cost: arranging a window takes far longer since there is more screen space to traverse and more relationships between windows to take into account. To address this we added ‘bumping’ to an application and tested it in a user study. Bumping allowed users to automatically move a window across multiple monitors. In this paper, we present our experiment contrasting three styles of bumping. We found less window repositioning required when users were given bumping in contrast to their existing practices. However we also found that simple implementations of intelligent bumping are not predictable, causing problems for our participants.